Literacy and Numeracy - How Does Music Fit into the Equation? - Smith, Robert G. (The Australian Journal of Indigenous Education, 2000)
Certainly in the past, and arguably continuing into the present, music education in schools has been and is often perceived as the exclusive domain of the so-called ‘talented and able’ with a distinct bias towards middle class West-centric society. Yet we are constantly reminded that education ought to address issues of inclusivity, access and equity for students, no matter what their background or history (Smith, 1995). In fact effective music education experiences often provide another means of access to learning areas such as language or maths for children excluded by their apparent lack of literacy or numeracy skills (Campbell, 2000).